2002
DOI: 10.1086/338075
|View full text |Cite
|
Sign up to set email alerts
|

The Near 160 Day Periodicity in the Photospheric Magnetic Flux

Abstract: A periodicity near 154 days was discovered in the number of high-energy solar Ñares detected by Solar Maximum Mission (SMM) and Geosynchronous Operational Environmental Satellites (GOES) during the time interval 1980È1984 (Rieger et al. ;Dennis). In this paper, we analyze the historical records of photospheric magnetic Ñux to show that during solar cycle 21 the periodicity appeared in the photospheric magnetic Ñux linked to strong magnetic Ðelds, while it was absent during solar cycle 22. We also show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
82
5
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 45 publications
8
82
5
2
Order By: Relevance
“…In particular, Rieger et al (1984) recognized a ≈154 day periodicity in X-ray flares during Cycle 21. Such "near-Rieger" periodicities have also been reported by, for example: Lean (1990) (who identified periods of ≈ 130-185 days in a survey of multiple sunspot cycles); Bai and Cliver (1990) (in proton-producing flares); Gonzalez et al (1993) (geomagnetic activity); Cane, Richardson, and von Rosenvinge (1998) (IMF and 25 MeV proton intensity in Cycle 21, including event clustering similar to that reported here); Dalla et al (2001) (SEP events in Cycle 23); Hill, Hamilton, and Krimigis (2001) (anomalous cosmic ray intensity in the outer heliosphere); Ballester, Oliver, and Carbonell (2004) (photospheric magnetic field); Richardson and Cane (2005) (SEP intensity, ICME and geomagnetic storm sudden commencement rate, hemispheric sunspot numbers, IMF); Lou et al (2003) and Lara et al (2008) (coronal mass ejections); and Lobzin, Cairns, and Robinson (2012) (solar type III radio bursts in Cycle 23). As discussed by several of these papers, in particular Lean (1990), these periodicities vary in strength and period both from cycle to cycle and within a given cycle.…”
Section: Summary and Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In particular, Rieger et al (1984) recognized a ≈154 day periodicity in X-ray flares during Cycle 21. Such "near-Rieger" periodicities have also been reported by, for example: Lean (1990) (who identified periods of ≈ 130-185 days in a survey of multiple sunspot cycles); Bai and Cliver (1990) (in proton-producing flares); Gonzalez et al (1993) (geomagnetic activity); Cane, Richardson, and von Rosenvinge (1998) (IMF and 25 MeV proton intensity in Cycle 21, including event clustering similar to that reported here); Dalla et al (2001) (SEP events in Cycle 23); Hill, Hamilton, and Krimigis (2001) (anomalous cosmic ray intensity in the outer heliosphere); Ballester, Oliver, and Carbonell (2004) (photospheric magnetic field); Richardson and Cane (2005) (SEP intensity, ICME and geomagnetic storm sudden commencement rate, hemispheric sunspot numbers, IMF); Lou et al (2003) and Lara et al (2008) (coronal mass ejections); and Lobzin, Cairns, and Robinson (2012) (solar type III radio bursts in Cycle 23). As discussed by several of these papers, in particular Lean (1990), these periodicities vary in strength and period both from cycle to cycle and within a given cycle.…”
Section: Summary and Discussionsupporting
confidence: 66%
“…The origin of the near-Rieger periodicity has been suggested to be near the surface of the Sun (Bai, 1987;Bai, 1988;Lou, 2000), due to changes in the rate of solar magnetic flux emergence (e.g., Cane, Richardson, and von Rosenvinge, 1998;Oliver, Ballester, and Baudin, 1998;Ballester, Oliver, and Carbonell, 2002) or a "global" phenomenon (e.g., Bai and Sturrock, 1987;Wolff, 1992), while Lean (1990) noted an association with complex active regions containing large sunspots ("super-active regions"). Recently, McIntosh et al (2015) have suggested that the variability in the number of flares, CMEs, particle events, and other solar and interplanetary phenomena is driven by surges of magnetism from activity bands of the 22-year solar cycle which are in turn driven by the deep solar interior.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In our Homestake article [1], we drew attention to the Rieger oscillation [40] (with a period of about 154 days) and related oscillations, which we here refer to as "Rieger-type" oscillations (for instance, oscillations with 72 day period and 51 day period) [41 -45]. The nature of these oscillations is still a matter of debate [45]. We have proposed [3] that they are due to internal r-mode oscillations [46 -48].…”
Section: Appendix B Indication Of Modulation At R-mode Frequenciesmentioning
confidence: 99%
“…The first of these oscillations was not discovered until 1984 (Rieger et al, 1984). Their characteristics and mechanism are still very much a matter of debate (Ballester, Oliver, and Carbonnel, 2002). A Rieger oscillation may be strong in one cycle and absent in the next (Bai, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Wavelet analyses show that they are typically transient and that the frequency is not constant (Ballester, Oliver, and Carbonnel, 2002;Rybak, Ozguc, Atak, and Sozen, 2005).…”
Section: Discussionmentioning
confidence: 99%